Using CIM Extensions to model Managed Entities in Heterogeneous Networks - Roque, Vítor (2012)
This paper is devoted to the definition of management information which models specific functionality of the entities that build Daidalos European Project. This management information will be used in policy–based management system (PBNMS) to manage QoS aspects of the network functionality.